Existence of Positive Solutions to Singular 𝑝-Laplacian General Dirichlet Boundary Value Problems with Sign Changing Nonlinearity - Qiying Wei; You-Hui Su; Subei Li; Xing-Xue Yan (Abstract and Applied Analysis)
By using the well-known Schauder fixed point theorem and upper and lower solution method, we present some existence criteria for positive solution of an 𝑚-point singular 𝑝-Laplacian dynamic equation on time scales with the sign changing nonlinearity. These results are new even for the corresponding differential (𝕋=ℝ) and difference equations (𝕋=ℤ), as well as in general time scales setting. As an application, an example is given to illustrate the results.